Does nest luminosity play a role in recognition of parasitic eggs in domed nests? A case study of the red bishop - Honza, Marcel; Šulc, Michal; Cherry, Michael I (Die Naturwissenschaften, 2014)
Certain light environments may hinder egg discrimination by hosts of foreign eggs, which could in some circumstances lead to the acceptance of non-mimetic eggs by hosts. We measured light parameters at red bishop (Euplectes orix) nests and used a model of avian visual processing to quantify the detectability of eggs in the light environment in which they are perceived. We found that the overall amount of light was very variable between red bishop nests and always sufficient for colour discrimination. A model of avian visual processing revealed that nest luminosity had no influence on host responses towards eggs which were painted dark brown. Dark eggs do not appear to be cryptic in red bishop nests and can be distinguished with ease, whereas natural red bishop eggs are usually accepted, despite the domed structure of the nest. We found little variation in both chromatic and achromatic contrasts between host and artificial eggs, indicating that there was very little variation in the light quality inside nests. We suggest that nest luminosity is likely to play a role in egg recognition in situations when light reaches threshold values for colour discrimination, i.e. in scotopic as opposed to photopic vision. Rejection rates for dark eggs were higher than for bright (conspecific) foreign eggs. More investigation of domed nest-building species is required, as this type of nest appears to have a highly variable light environment, dependent on both nest structure and habitat.
Keywords: druhová specificita; Nesting Behavior; Recognition, Psychology; světlo; Ecosystem; Color; zraková percepce; Host-Parasite Interactions; vaječná skořápka; Parasites; zvířata; Visual Perception; Light; Ovum; hnízdění; barva; Species Specificity; rozpoznávání (psychologie); ovum; Egg Shell; Passeriformes; Animals; interakce hostitele a parazita; paraziti; ekosystém